PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK MULTILEVEL MARKETING (Studi Pada PT. Sinar Nusa Indonesia Di Kota Semarang) - Afiani, Lia; Lubis, Nawazirul; Wijayanto, Andi (Jurnal Ilmu Administrasi Bisnis, 2014)
PT. Sinar Nusa Indonesia (SNI) is an Indonesian company using multilevel marketing techniques, that sells a variety of products, primarily in the health and home care market. A company using marketing mix strategy (product, price, place and promotion) to increase purchasing decision, but can’t reached the sales target. The purpose of this study was to determine the effect of marketing mix to purchase decision of PT. SNI product. This type of research used to be an explanation (explanatory research). The research is determined by using a purposive random sampling with sample 100 respondents. Analysis technique using linier regression analysis. From analysis can be concluded as follows : a) There is a positive and significant influence of the product to the purchasing decision, b) There is a positive and significant influence of the price to the purchasing decision, c) There is a positive and significant influence of the place to the purchasing decision, d) There is a positive and significant influence of the promotion to the purchasing decision, e) There is a significant influence of the marketing mix to the purchasing decision. Simultaneously, marketing mix influence purchasing decision with contribution 49,1 %.The conclution of this research is marketing mix influence purchase decision MLM product of PT. SNI. Suggestion posed for this research is necessary to the product’s quality and variation by making innovation of new product in order not to bore customer. A company might increase efficiency to reach a better price of the product. Make any creative promotion by adding reward is also needed to increase customer purchase decision.